Migrant Families, Social Policies and Community Relations: Towards What (Kind Of) Integration? - Di Rosa, Roberta Teresa; Allegri, Elena (Italian Sociological Review, 2022)
This article aims to present a few considerations regarding the phenomenon of migrant families’ integration processes, in the broader framework of the relationship between politics, policies and services. The stabilization of migrant people in Italy has determined, on the one hand, the growth of the family-based character of the immigrant population, in the face of which, institutions and reception services, in the wake of policy directives, have been called upon to remodel interventions and integration practices. On the other hand, the drastic reduction in political attention to the social, civil and economic integration of migrants and, in particular, of migrant families, linked to the direction taken by migration policies, has had serious effects in terms of social inclusion. The effects of “unsupportive” policies towards migrants have generated major obstacles to integration (ISTAT, 2021), that are added to, exacerbating them, the crisis caused by the pandemic has exacerbated the fragility of migrant families. There has been a fall-out on integration processes, in which the family, the network of relationships and social and socio-medical services play a fundamental role. [...]